p-Quinol Ethers and p-Quinone Monoacetals as Arylation and Oxidation Reagents: Tandem N-Arylation and α-Functionalization of Pyrrolidine via Redox-Neutral Three-Component Reaction - Li, Xiaojie; Xie, Yuxin; Yin, Kaixin; Shen, Ruwei; Zhu, Dunru (Synthesis, 2022)
The value of functional pyrrolidines in the fields of biology, pharmacology, catalysis, and natural product synthesis stimulates an intensive interest in developing new synthetic methods for this class of compounds, and direct functionalization of the simple pyrrolidine represents an attractive and effective approach. Herein, a metal-free protocol for direct N-arylation and α-functionalization of pyrrolidine via redox-neutral three-component reactions is reported, in which p-quinol ethers or p-quinone monoacetals serve as the arylation components and the formal oxidants for α-functionalization of pyrrolidine.
Keywords: pyrrolidine; redox-neutral MCR; N-arylation; phosphinylation; α-functionalization